Development of GIS-based classroom management information system in UiTM / Noraini Ismail, Abdul Rauf Abdul Rasam and Mohd Halmi Kamaruddin - Ismail, Noraini; Abdul Rasam, Abdul Rauf; Kamaruddin, Mohd Halmi (2012)
Universiti Teknologi MARA (UiTM) is Malaysia's largest institution of higher learning in terms of size and population; consequently it needs an efficient database building information model (BIM) in managing classroom and other facilities. Geographical information system (GIS) is one of the tools that have the capability for such application today. Therefore, this study is to develop a proposed classroom management information system in the Centre of Studies Surveying Science and Geomatics (PPSUG,) UiTM Shah Alam using GIS, Microsoft Visual Basic (VB) and MapObjects Windows. The integration of BIM and GIS technologies not only opens up a suite of new analysis options for facility operators, but also allows the results of these analyses to be reported and visualized at all geographic levels of detail. The Standard System Development Lifecycle (SDLC) is adapted to achieve the objectives of study; i) to analyze the user requirement on the proposed system; ii) to design and develop the system; and iii) to implement and evaluate the system. 90% of the selected respondents strongly agree that the existing classroom system should be improved with dynamic query functions, mapping direction, graphical visualization, and printing functions. This proposed system allows the user to have a dynamic view and search the spatial classroom information. The result of study could be used by the Department of Facility Management and PPSUG as a geospatial framework for Sustainable Classroom Management Information System (SuCeS) in UiTM